Intermediate education schools in Al- Aziziya district center analysis Geographical - Kareem Jnait, Mohammed (Journal of College of Education, 2021)
The research aims to study the of the reality of Intermediate education schools in the district Aziziya center, and evaluate educational indicators efficiency according to the local planning standards to reach the reality of education, and was it taken by these standards? Or is the process conducted by methods and methods that represent the reality and disposal of existing educational indicators, whether it is efficient or not efficient that the research adopted in Contemporary phase of the academic year 2019-2020. The research achieved concluded the most important results it is the large deficit in the number of school buildings for both sectors, and thus an increase in the number of the students in one school, as well as a variation of efficiency in relation to the average number of the students in one building, as well as the average number of the students in one section and the increase the rate of one teacher share from the students Which was the result of an deficiency in the number of members of the teaching staff body than the required number, which amounted to an deficiency of (%19.5) and (%8.8) in the first and second sectors .